Dinamika Perkembangan Madrasah Nurul Falah Palembang Pada Tahun 1352-1371 H / 1934-1952 M - Resti Ayu Widianti (Tanjak: Sejarah dan Peradaban Islam, 2022)
Islamic education is one of the means carried out to guide, direct and foster students by the values of Islamic teachings. This study discusses the History and Development of Nurul Falah Islamic School Palembang which is interesting to study, in South Sumatra the emergence of Islamic School is due to external factors that influence it. External factors can be seen from the existence of western schools which were established by the colonial government. Western schools tend to be based on general lessons with non-Islamic. This has made the ulama figures in South Sumatra want to compete with western schools by establishing Islamic-based schools in which they not only study general knowledge but also religion. The school was established to be able to compete with western schools. One of the schools that pioneered the existence of Islamic schools in South Sumatra is Nurul Falah Islamic School. The purpose of this study was to determine the dynamics of the development of Nurul Falah Islamic School Palembang how the history and development of the Islamic School. In this case, the history of the establishment of this Islamic School is related to the existence of western schools so that the ulama figure KH. Abubakar Bastari tried to compete with western schools by establishing Nurul Falah Islamic School Palembang.